PENGARUH PRODUCT INNOVATION, PRODUCT QUALITY DAN BRAND IMAGE TERHADAP CUSTOMER LOYALTY DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING DI PT. INSERA SENA - Rosita Septiani; Wan Dismarita (Postgraduate Management Journal, 2023)
This research is conducted to analyze the effect from product innovation, product quality, and brand image (brand strength, brand favorable dan brand uniqueness) to customer loyalty, with consideration factors of competitive advantage (price, quality, variety, distribution and innovation). The research was conducted with questionnaire to one hundred respondent. This research was conducted by distributing questionnaires to 50 respondents who use Polygon bikes. Type of this research is causal research with quantitative analysis using path analysis technique.